As medidas estruturantes no direito à saúde no Brasil - Reichert, Vanessa (Universidade do Vale do Rio dos Sinos, 2015)
By combining the study of the right to health with the structural reforms, this study aims to find out if there is a possibility to the Brazilian judiciary determine structural reforms in the health field through Public Civil Action. It is known that although health is a social fundamental right in Brazil since the 1988 Federal Constitution, its effectiveness in terms of the facts is far from ideal. The inertia of the government and the state bureaucracies, coupled with expectations of the population have made the judiciary, by the demand knocking on their door, be called to consummate this right constitutionally guaranteed. Aware of this, specifically, the objective is to study the feasibility of civil associations prosecute Public Civil Action to require for state entities the implementation of a health center or a unit of emergency care in your community, for example, when it is common knowledge that the state is inert to the request and the need for a long time. In conclusion to this study, it is understood that the Public Civil Action with the tutelage of to do, not do and deliver provided things in the current Civil Code and maintained in the new civil procedure law, which will come into force next year, enable the entry of US judicial decision model started in the 50s of the last century at the Warren Court and Owen Fiss doctrine to Brazilian law, and the article 139 of the New Civil Procedure Code further extends this possibility. The proposal, presented at the end, is in the sense that the structural reforms can be implemented by Public Civil Action, when, for example, people living in the poorest communities and are victims of repeated omission of the Government to effect the right to health, could constitute an association with the purposes required by the Law and so, using the legitimate and democratic instrument that is the PCA to, plead in court, the defense of the collective interests of their group, requiring the implementation of a health center in their community, for example. Regarding to the methodology, the research used the hermeneutical-philosophical method approach to reconstruct the object, rethinking it from the proposed objectives.
Keywords: Direitos sociais; Direito à saúde; Medidas estruturantes; Ação civil pública; Social rights; Right to health; Structural reforms; Public civil action; ACCNPQ::Ciências Sociais Aplicadas::Direito